2009
DOI: 10.1194/jlr.m800533-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Reducing CYP51 inhibits follicle-stimulating hormone induced resumption of mouse oocyte meiosis in vitro

Abstract: This article is available online at http://www.jlr.orgMammalian oocytes arrested at the diplotene stage of the fi rst meiotic division are triggered to initiate meiosis by the preovulatory gonadotrophin surge in vivo, especially LH surge ( 1, 2 ). It has recently been suggested that certain intermediates of cholesterol biosynthesis, such as meiosis activating sterol (MAS), one of the upstream materials for synthesize of steroid hormones, instruct the oocyte to reinitiate meiosis ( 3-6 ). In invertebrate animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Recent research has further elucidated a connection between RA regulation of Rec8 and CYP51 (Mu et al, 2018). FF-MAS itself was considered to be meiosis-inducing substance secreted by fetal ovaries, which could induce meiosis in fetal male germ cells (Byskov & Saxen, 1976), and had capacity to reinitiate meiotic resumption in mice oocytes in vitro (Wang et al, 2009 FF-MAS itself was considered to be meiosis-inducing substance secreted by fetal ovaries, which could induce meiosis in fetal male germ cells (Byskov & Saxen, 1976), and had capacity to reinitiate meiotic resumption in mice oocytes in vitro (Wang et al, 2009 …”
Section: Meiosis Induction In Fetal Ovarymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has further elucidated a connection between RA regulation of Rec8 and CYP51 (Mu et al, 2018). FF-MAS itself was considered to be meiosis-inducing substance secreted by fetal ovaries, which could induce meiosis in fetal male germ cells (Byskov & Saxen, 1976), and had capacity to reinitiate meiotic resumption in mice oocytes in vitro (Wang et al, 2009 FF-MAS itself was considered to be meiosis-inducing substance secreted by fetal ovaries, which could induce meiosis in fetal male germ cells (Byskov & Saxen, 1976), and had capacity to reinitiate meiotic resumption in mice oocytes in vitro (Wang et al, 2009 …”
Section: Meiosis Induction In Fetal Ovarymentioning
confidence: 99%
“…CYP51 catalyzes the conversion of lanosterol to follicular fluid meiosis-activating sterol (FF-MAS) (Stromstedt et al, 1998). FF-MAS itself was considered to be meiosis-inducing substance secreted by fetal ovaries, which could induce meiosis in fetal male germ cells (Byskov & Saxen, 1976), and had capacity to reinitiate meiotic resumption in mice oocytes in vitro (Wang et al, 2009)…”
Section: Meiosis Induction In Fetal Ovarymentioning
confidence: 99%
“… 24 , 25 , 26 Thus, understanding the mechanisms of FSH and LH controlling follicular development and oocyte maturation is critical for improving the effectiveness of assisted reproduction techniques (ARTs) in clinical applications. In addition, series of studies have indicated that FSH alone is sufficient to induce oocyte maturation in vitro , 27 , 28 , 29 , 30 which is contradictory with that in vivo . However, the related mechanisms are poorly understood.…”
mentioning
confidence: 99%
“…The knockdown of CYP51 expression via siRNAs inhibited FSH-, but not LH-induced meiosis in mouse oocytes (Wang et al, 2009a). Furthermore, cultured mouse oocyte-granulosa cell complexes injected with siRNAs of mouse zona pellucida glykoprotein A (ZpA) had reduced growth and survival and abnormal morphology of zona pellucida.…”
Section: Rna Interference and Oocyte Maturationmentioning
confidence: 99%